Invasive pneumococcal pneumonia caused by 13-valent pneumococcal conjugate vaccine types in children with different schedules - Hong-Yi Lee; Yu-Chia Hsieh; Ching-Chuan Liu; Yi-Chuan Huang; Kuang-Yi Chang; Hsin Chi; Luan-Yin Chang; Yhu-Chering Huang; Li-Min Huang (Journal of Microbiology, Immunology and Infection, 2018)
Background: In Taiwan, the age group with the greatest incidence of invasive pneumococcal disease is 2–5 years of age, which is different from other countries. This study was conducted to identify risk factors and different 13-valent pneumococcal conjugate vaccine (PCV13) schedules associated with vaccine-type invasive pneumococcal pneumonia (IPP) despite prior vaccination. Methods: A case–control study was conducted prospectively between August 2012 and December 2015 at five participating medical centers. The study enrolled children <15 years of age who were admitted to one of the five medical centers for CAP. Blood samples and acute-phase serum specimens were collected and Streptococcus pneumoniae was identified by using a real-time polymerase-chain-reaction (RT-PCR) assay targeting the lytA gene. Results: A total of 25 children diagnosed with vaccine-type IPP and 124 controls were enrolled. Vaccine-type IPP occurred in 6 (28.6%), 14 (24.1%), and 5 (7.1%) children receiving vaccines on a not-age-appropriate schedule (n = 21), primary infant schedule (n = 58), and toddler catch-up schedule (n = 70) (P = 0.008), respectively. Of 25 children, the mean age at disease onset was 36 ± 11 months; serotype 19A was responsible for 84% (21/25). Conclusion: After adjustment for confounding factors, the risk of vaccine-type IPP was significantly higher among children receiving vaccines on a not-age-appropriate schedule, or on a primary infant schedule, compared with children receiving vaccines on a toddler catch-up schedule. Duration of vaccine immunity should be investigated to direct strategies for maintaining individual and population immunity against pneumococcal disease. Keywords: 13-Valent conjugate pneumococcal vaccine, Invasive pneumococcal pneumonia, Vaccine schedule